Flow-assisted basophil activation tests in immediate drug hypersensitivity: two decades of Antwerp experience. Issue 1 (2nd January 2016) - Mangodt, E. A.; Van Gasse, A. L.; Bastiaensen, A.; Decuyper, I. I.; Uyttebroek, A.; Faber, M.; Sabato, V.; Bridts, C. H.; Hagendorens, M. M.; De Clerck, L. S.; Ebo, D. G.
Abstract : The last two decades have witnessed that flow-assisted analysis of in vitro- activated basophils can constitute a valuable adjunct in the in vitro diagnostic approach of immediate drug hypersensitivity reactions (IDHR). This article summarises the current experience with the basophil activation test in the diagnosis of IDHR, with particular focus on allergy to curarising neuromuscular blocking agents, antibiotics (β-lactams and fluoroquinolones), iodinated radiocontrast media and opiates.